cBid, Bax and Bcl-xL exhibit opposite membrane remodeling activities - Bleicken, Stephanie; Hofhaus, Götz; Ugarte-Uribe, B.; Schröder, Rasmus R.; García-Sáez, Ana J. (Cell death & disease, 2016)
The proteins of the Bcl-2 family have a crucial role in mitochondrial outer membrane permeabilization during apoptosis and in the regulation of mitochondrial dynamics. Current models consider that Bax forms toroidal pores at mitochondria that are responsible for the release of cytochrome c, whereas Bcl-xL inhibits pore formation. However, how Bcl-2 proteins regulate mitochondrial fission and fusion remains poorly understood. By using a systematic analysis at the single vesicle level, we found that cBid, Bax and Bcl-xL are able to remodel membranes in different ways. cBid and Bax induced a reduction in vesicle size likely related to membrane tethering, budding and fission, besides membrane permeabilization. Moreover, they are preferentially located at highly curved membranes. In contrast, Bcl-xL not only counterbalanced pore formation but also membrane budding and fission. Our findings support a mechanism of action by which cBid and Bax induce or stabilize highly curved membranes including non-lamellar structures. This molecular activity reduces the energy for membrane remodeling, which is a necessary step in toroidal pore formation, as well as membrane fission and fusion, and provides a common mechanism that links the two main functions of Bcl-2 proteins.